Penampilan Beberapa Genotip Kedelai Hasil Seleksi pada Lingkungan Ternaungi di Bawah Tegakan Karet - Alia, Yulia; Soverda, Nerty; Lestari, Ardiyaningsih Puji; Fitriani, Miranti Sari (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2018)
Research was aimed to evaluate performance of new genotypes of soybean selected in shaded environment under rubber stands and compare it with superior soybean varieties. Field experiment was arranged in a simple Randomized Block Design. Treatments comprised five levels namely four soybean genotypes selected in artificial shade and one shade tolerant superior soybean variety as a check. Each treatment was replicated 5 times. Experimental unit was a plot with size 3 m x 2 m with 100 plant population. Ten plants were used as samples. Observations were made on growth and yield variables. Such variables were plant height, number of branches, and stem diameter, while the observed yield variables included number of pod per plant, 100 seed weight, and seed weight of 10 plants. Observed data were analyzed by Analysis of Variance and continued by Duncan Multiple Range Test at Î± 5% level to compare the tested genotypes. Results showed that all the tested soybean genotypes gave the same performance with superior varieties of Anjasmoro in terms of stem diameter, number of branches, number of pods per plant, weight of 100 seeds, and seed weight of 10 stems of the plant. The difference was seen in of plant height where the selection genotypes were significantly shorter than Anjasmoro Variety.